2012
DOI: 10.4236/fns.2012.36114
|View full text |Cite
|
Sign up to set email alerts
|

Edible Seeds and Nuts Grown in Brazil as Sources of Protein for Human Nutrition

Abstract: Edible seeds and nuts can contribute to an adequate intake of protein, particularly in vegetable-based diets. However, there are relatively few reports with insufficient data regarding the protein quality of these foods, especially of edible seeds and nuts from Brazil. The aim of this study was to investigate the chemical composition and <i>in vivo</i> protein quality of two edible seeds (baru almond and peanut) and two nuts (Brazil nut and cashew nut) grown in Brazil. The proximate composition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 14 publications
5
20
0
4
Order By: Relevance
“…We observed high protein (309 g•kg −1 ) and lipid (412 g•kg −1 ) contents in baru almonds, with no significant differences among regions ( Table 3). These high amounts of protein and lipid of the baru almond are supported by the literature [6,8,23]. Protein contents of baru almonds were slightly higher than those of traditional nuts studied by Venkatachalam and Sathe [24], and the lipid contents ( Table 3) were lower than those of the brazil nut, hazelnut, macadamia nut, pecan, pine nut, and walnut, which contain approximately 600 g•kg −1 [24].…”
Section: Nutrient Compositionsupporting
confidence: 71%
See 1 more Smart Citation
“…We observed high protein (309 g•kg −1 ) and lipid (412 g•kg −1 ) contents in baru almonds, with no significant differences among regions ( Table 3). These high amounts of protein and lipid of the baru almond are supported by the literature [6,8,23]. Protein contents of baru almonds were slightly higher than those of traditional nuts studied by Venkatachalam and Sathe [24], and the lipid contents ( Table 3) were lower than those of the brazil nut, hazelnut, macadamia nut, pecan, pine nut, and walnut, which contain approximately 600 g•kg −1 [24].…”
Section: Nutrient Compositionsupporting
confidence: 71%
“…However, almonds from the different plants of the Southeast region of the Brazilian Savanna (Goiás State) presented only a slight deficiency in sulphur-containing amino acids (AAS = 90%) or lysine (AAS = 97%), depending on the plant that baru almond came from [6]. In another study, the baru almond from the West region of the Brazilian Savanna showed a relatively higher deficiency in lysine (AAS = 75%) [8].…”
Section: Introductionmentioning
confidence: 93%
“…Cashew nuts present high protein levels (23%) with all the essential amino acids for humans, and lipids (44%) (Freitas et al, 2012), with mono and polyunsaturated fatty acids being the major components (Adjepong et al, 2017). As such, they are a distinct matrix possibility for probiotic delivery.…”
Section: Introductionmentioning
confidence: 99%
“…and pequi tree (Caryocar brasiliense Camb.) and native species of the Cerrado with great commercial and technological potential 1 Edible seeds and nuts contain high levels of lipids and proteins and a good essential amino acid profile, although containing a slight deficiency of lysine, methionine, and cysteine [1][2][3] . They also have a considerably high contents of dietary fiber and minerals 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…and native species of the Cerrado with great commercial and technological potential 1 Edible seeds and nuts contain high levels of lipids and proteins and a good essential amino acid profile, although containing a slight deficiency of lysine, methionine, and cysteine [1][2][3] . They also have a considerably high contents of dietary fiber and minerals 2,3 . Furthermore, these oilseeds stand out due to their fatty acid profile, particularly oleic (C18:1ω9) and linoleic (C18:2ω6) acids 4,5 , and due to their high concentrations of phytosterols and phenolic compounds and high contents of vitamin E 6,7 .…”
Section: Introductionmentioning
confidence: 99%